2006
DOI: 10.1002/jhet.5570430622
|View full text |Cite
|
Sign up to set email alerts
|

Microwaves in organic synthesis: Synthesis of pyridazinones, phthalazinones and pyridopyridazinones from 2‐oxo‐arylhydrazones under microwave irradiation

Abstract: The phenylhydrazones 1a‐d condensed with ethyl cyanoacetate to yield pyridazinones 2a‐d that reacted with sulphur in presence of piperidine to yield the aminothienopyridazineones 3a,b that reacted with electron poor olefins and acetylenes to yield phthalazines 10‐12. The condensed aminothiophenes 3a,b reacted with dimethylformamide dimethylacetal to yield amidines 13a,b. Compounds 2a,b condensed with dimethylformamide dimethylacetal to yield the trans enamines 16a,b that cyclized readily into the pyridopyridaz… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
17
0

Year Published

2007
2007
2016
2016

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 17 publications
(18 citation statements)
references
References 17 publications
1
17
0
Order By: Relevance
“…Additional studies showed that chitosan also catalyzes condensation reactions between benzaldehyde, malononitrile and pyridazinone 26 yielding the pthalazinone 28 (Scheme 7) that was reported [17] earlier to be produced in pyridine assisted reactions of the substrates. We believe that the initial step in this process involves benzaldehyde condensation with malononitrile to yield benzylidene-malononitrile, a reaction that has been reported to occur under mild conditions [18,19].…”
Section: Resultsmentioning
confidence: 80%
“…Additional studies showed that chitosan also catalyzes condensation reactions between benzaldehyde, malononitrile and pyridazinone 26 yielding the pthalazinone 28 (Scheme 7) that was reported [17] earlier to be produced in pyridine assisted reactions of the substrates. We believe that the initial step in this process involves benzaldehyde condensation with malononitrile to yield benzylidene-malononitrile, a reaction that has been reported to occur under mild conditions [18,19].…”
Section: Resultsmentioning
confidence: 80%
“…We have found that arylhydrazonal derivative (1h) reacts with malononitrile (6) and aromatic aldehyde (7a-e) to yield the pyridazinonaphthyridine derivatives (8a-e) (Scheme 2).…”
Section: Resultsmentioning
confidence: 99%
“…Although, in a previous article, Moustafa et al [18] reported the formation of pyridazino [5,4,3-de] [1,6]naphthyridine derivatives via reaction of ethyl 3-oxo-2-arylhydrazono butanoate, malononitrile and aromatic aldehydes under high pressure but they could not conclude exact mechanism of the process leading to the formation of the tricyclic system. In our efforts described above the reactions are also conducted in a Q-tube, as in more than one situation, products resulting from initial condensation with malononitrile as the case of compound 1j and 1k and subsequent reaction with arylidene malononitrile have been observed which decisively excluded the initial dimerization of malononitrile.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations